Pengaruh Sales Promotion, Hedonic Shopping Motivation Dan Web Quality Terhadap Impulse Buying Pada Online Shop Shopee Di Masa Pandemi (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Syifaullima Fissudur; Muhammad Ridwan Basalamah; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to explain the effect of sales promotion, hedonic shopping motivation and web quality on impulse buying at Shopee's online shop. The variables used in this study consist of 4 variables, namely the dependent variable is impulse buying and the independent variables are sales promotion, hedonic shopping motivation, and web quality. The data used are primary and secondary data, obtained from students of the Faculty of Economics and Business, Islamic University of Malang. Sampling was done using purposive sampling method. Data analysis used classical assumption test and multiple linear regression. The results of this study indicate that the variables of sales promotion, hedonic shopping motivation and web quality have a positive effect on impulse buying for FEB UNISMA students. While Sales Promotion, Hedonic Shopping, Web Quality have a positive effect on Impulse Buying on Shopee's online shop. Keywords: Impulse buying, sales promotion, hedonic shopping motivation, and web quality